2015
DOI: 10.1007/s40725-015-0025-5
|View full text |Cite|
|
Sign up to set email alerts
|

Terrestrial Laser Scanning for Plot-Scale Forest Measurement

Abstract: Plot-scale measurements have been the foundation for forest surveys and reporting for over 200 years. Through recent integration with airborne and satellite remote sensing, manual measurements of vegetation structure at the plot scale are now the basis for landscape, continental and international mapping of our forest resources. The use of terrestrial laser scanning (TLS) for plot-scale measurement was first demonstrated over a decade ago, with the intimation that these instruments could replace manual measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
190
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(198 citation statements)
references
References 73 publications
4
190
0
4
Order By: Relevance
“…Low sampling of the understory due to insufficient aerial LiDAR penetration can be overcome by terrestrial LiDAR, which allows a much denser sampling pattern. It may also ultimately provide robust leaf area index estimates as it has the potential to separate leaf from non-leaf material (Raumonen et al 2013;Calders et al 2015;Newnham et al 2015) and to provide a more accurate description of the spatial arrangement of the foliage (clumping and orientation). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Low sampling of the understory due to insufficient aerial LiDAR penetration can be overcome by terrestrial LiDAR, which allows a much denser sampling pattern. It may also ultimately provide robust leaf area index estimates as it has the potential to separate leaf from non-leaf material (Raumonen et al 2013;Calders et al 2015;Newnham et al 2015) and to provide a more accurate description of the spatial arrangement of the foliage (clumping and orientation). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of multiple scanner positions reduces the occlusion in a stand substantially [17,34,42,43]. Based on scanner location patterns found in the literature, we simulated 25 single scanning positions on each sample plot (n = 536) (see Figure 4) and combined them to form a total of 40 scanning location patterns (see Figures A2 and A3 in the Appendix A).…”
Section: Influence Of Scanner Location Pattern On Visibility In a 2d mentioning
confidence: 99%
“…For these objects, only multiple TLS measurements can improve the coverage, albeit in a linear fashion. Newnham et al [42] identify two different categories of data retrieval approaches from TLS generated point clouds: gap probability and geometrical modelling. While the former approach samples the forest scene to provide a complement of all vegetation components, the latter uses the discrete point clouds to derive geometrical properties of the scanned object, e.g., by quantitative structure modelling (QSM) [44,45].…”
Section: Theoretical Coverage Of a Laser Scanning System In A 3d Spacementioning
confidence: 99%
“…Compared with airborne laser scanning and field measurements, TLS can obtain accurate understory information, including a digital record of the three-dimensional structure of forests [3]. Many studies have demonstrated the high potential of TLS in forest inventory, including tree locations [1,[4][5][6], heights [2,3,7], diameters [2,3,6,[8][9][10][11][12][13][14][15], volumes [16][17][18], biomass [17,[19][20][21][22][23] and others forestry parameters [24][25][26][27]. In addition, the influence of scanner parameters on forestry parameter derivation has been studied [18,28].…”
Section: Introductionmentioning
confidence: 99%